Recreational Reading Habits of the EFL Pre-Service Teachers in an Indonesian Islamic Higher Education - Ruslin, Ruslin; Asmawati, Nur; Thuratham, Wadinlada; Syahid, Ahmad; Tamrin, Mukrim; Syam, Hijrah; Shakti, Tendri Sanna (FKIP Universitas Lampung, 2025)
Recreational Reading Habits of the EFL Pre-Service Teachers in an Indonesian Islamic Higher Education. Objectives: This study aims to investigate the recreational reading habits of EFL pre-service teachers at Islamic universities, with a focus on the relationship between the duration of recreational reading and academic achievement. Furthermore, this study also examines differences in reading time based on gender, age, level of study, and students' reading preferences. Methods: This research employed a mixed-methods approach through a cross-sectional survey design and case study, involving 56 students from three classes of the English Language Education Study Program at UIN Datokarama Palu. Data were collected through an online survey, semi-structured online interviews, and document analysis. These data were then analyzed using descriptive and inferential statistics, as well as thematic analysis, to explore quantitative patterns and qualitative meanings in depth. Findings: The results of the study showed that involvement in recreational reading activities had a very moderate relationship with the academic achievement of the EFL preservice teachers, indicating that although recreation reading may increase their language awareness and learning motivation, its direct impact on academic achievement was still relatively limited. It was found that 50% of the respondents read for less than one hour per week, reflecting low levels of recreational reading engagement. Differences were also evident based on demographics, with female students and younger age groups tending to read more frequently and preferring digital texts and short reading materials such as online stories and motivational content. Despite limited reading time, students who regularly engage in recreational reading demonstrate better academic achievement, wider vocabulary mastery, and positive attitudes towards learning English. Conclusion: This study confirms the importance of recreational reading culture in supporting academic success, independent learning, and long-term intellectual development. Islamic universities are expected to foster a culture of reading for pleasure by integrating it into the curriculum, strengthening library facilities, and utilizing digital platforms. Keywords: pre-service EFL teachers, recreational reading habits, reading for pleasure.